The virtuous emulsification of business and nutrition: why bother and ways forward - Haddad, Lawrence (2016)
Lawrence Haddad 26th Annual Martin J. Forman Memorial Lecture The Virtuous Emulsification of Business and Nutrition: Why Bother and Ways Forward